2007
DOI: 10.1007/s00421-007-0634-1
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic cardiovascular control during orthostatic stress and isometric exercise in adolescent chronic fatigue syndrome

Abstract: The chronic fatigue syndrome (CFS) has been shown to be associated with orthostatic intolerance and cardiovascular dysregulation. We investigated the cardiovascular responses to combined orthostatic stress and isometric exercise in adolescents with CFS. We included a consecutive sample of 15 adolescents 12-18 years old with CFS diagnosed according to a thorough and standardized set of investigations, and a volunteer sample of 56 healthy control subjects of equal sex and age distribution. Heart rate, systolic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
51
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 41 publications
11
51
0
Order By: Relevance
“…31 Other studies have demonstrated that the change of posture may lead to an abnormal cardiovascular response (orthostatic hypotension, POTS, syncope) in one-third of patients 32,33 and that CFS is most likely associated with sympathetic dysfunction. 34 There are also studies supporting the similarity of the autonomic dysfunctions observed in CFS and POTS. 35,36 Hägglöf 37 in 2000 and Björkegren 38 in 1999 demonstrated that CFS could be treated with vitamin B 12 .…”
Section: Discussionmentioning
confidence: 87%
“…31 Other studies have demonstrated that the change of posture may lead to an abnormal cardiovascular response (orthostatic hypotension, POTS, syncope) in one-third of patients 32,33 and that CFS is most likely associated with sympathetic dysfunction. 34 There are also studies supporting the similarity of the autonomic dysfunctions observed in CFS and POTS. 35,36 Hägglöf 37 in 2000 and Björkegren 38 in 1999 demonstrated that CFS could be treated with vitamin B 12 .…”
Section: Discussionmentioning
confidence: 87%
“…Although some authors suggest that the response of CFS patients to passive verticalization is similar to that of healthy individuals, it has been shown that the activation of the sympathetic nervous system can be more pronounced as was documented in our patient [15][16][17][18][19][20][21][22][23]. The evaluation of chronic fatigue syndrome remains challenging.…”
Section: Discussionmentioning
confidence: 57%
“…Treatment of orthostatic intolerance symptoms with fludrocortisone, however, in all studies did not reduce symptoms of fatigue in patients with chronic fatigue syndrome [2,22]. Recently, studies on the increased sympathetic activity in patients with chronic fatigue and orthostatic intolerance were published, suggesting a possible beneficial role for beta-blockers in this patient group [36,37]. These, and other treatment options, still have to be studied in this specific patient group.…”
Section: J Interpretationmentioning
confidence: 96%